Four new records and a new species of Cucurbitaceae for the Flora of Oaxaca - Lira Saade, Rafael; Torres Colin, Rafael (Instituto de Ecología, A.C., 1991)
Four species of Cucurbitaceae (Tecunumania quetzalteca Standley & Steyemark, Cionosicyos macanthus (Pittier) C. Jeffrey, Peponopsis adhaerens Naudin y Chalema synanthera Dieterle) are reported for the first time for the flora of Oaxaca (the latter also for Guerrero) and a new species of Parasicyos Dieterle is described.